Association between insulin resistance indices and kidney stones: results from the 2015–2018 National Health and Nutrition Examination Survey - Shen, Yue; Zhu, Zhu; Bi, Xiao; Shen, Yuqi; Shen, Aiwen; Deng, Bo; He, Yining; Wang, Wenji; Ding, Feng (Frontiers in Nutrition, 2024)
Objective: To explore the association between representative insulin resistance (IR) indices and the risk of kidney stone disease in an American adult population. The representative IR indices referred to metabolic score for IR (METS-IR), triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio, triglyceride glucose-body mass index (TyG-BMI), visceral adiposity index (VAI), and homeostatic model assessment of IR (HOMA-IR). Methods: We investigated adult participants who joined the 2015–2018 National Health and Nutrition Examination Survey (NHANES) and reported kidney stone histories. Weighted proportions, multivariable regression analysis, and restricted cubic splines were used to evaluate the associations between IR indices and kidney stones after their adjustment for gender, age, race, education, smoking status, alcohol drinking frequency, hypertension and diabetes status, physical activity level, water intake, and levels of calcium, cholesterol, and uric acid. Results: A total of 19,225 participants were included. The weighted prevalence of kidney stone was 11.1%. A multivariable logistic regression model showed a dose-response relationship between the METS-IR and kidney stone [odds ratio (OR) = 1.02, 95% confidence interval (CI) (1.01, 1.04), P <.01]. A similar relationship was observed between the TyG-BMI and kidney stone after full adjustment [OR = 1.0, 95% CI (1.0, 1.01), P <.001]. Sex-stratified analyses revealed that the association between METS-IR and nephrolithiasis [OR = 1.03, 95% CI (1.01, 1.05), P <.01], and the association between TyG-BMI and nephrolithiasis [OR = 1.01, 95% CI (1.0, 1.01), P ＜.001] was significant among the male participants in the fully adjusted model. Moreover, a significant association was found between the METS-IR levels and nephrolithiasis [OR = 1.03, 95% CI (1.01, 1.06), P <.01], and between the TyG-BMI levels and nephrolithiasis [OR = 1.01, 95% CI (1.0, 1.01), P <.05] among the diabetic participants after full adjustment. Furthermore, a potential nonlinear association was found between other IR indices (i.e., TG/HDL-C, VAI, and HOMA-IR) and the risk of kidney stone disease. Conclusion: Higher METS-IR and TyG-BMI levels were associated with a higher risk of nephrolithiasis. Future investigations are required to identify the role of IR in the progress of kidney stone formation and to propose prevention measures and health guidelines.